2018
DOI: 10.1177/2331216518778651
|View full text |Cite
|
Sign up to set email alerts
|

Age, Hearing, and the Perceptual Learning of Rapid Speech

Abstract: The effects of aging and age-related hearing loss on the ability to learn degraded speech are not well understood. This study was designed to compare the perceptual learning of time-compressed speech and its generalization to natural-fast speech across young adults with normal hearing, older adults with normal hearing, and older adults with age-related hearing loss. Early learning (following brief exposure to time-compressed speech) and later learning (following further training) were compared across groups. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 92 publications
(173 reference statements)
18
40
1
Order By: Relevance
“…Although highly compressed speech is initially hard to recognize, recognition accuracy improves quite rapidly with exposure to as few as 10 to 20 time-compressed sentences (e.g., Dupoux & Green, 1997;Golomb et al, 2007). This rapid learning has been shown in young and in older adults as well as in older adults with hearing impairments (Golomb et al, 2007;Manheim et al, 2018;Peelle & Wingfield, 2005). Finally, across age and hearing levels, we previously reported that variance in rapid learning of TCS accounted for unique variance in the recognition of NFS, even after controlling for the known association between the recognition of NFS and TCS (Manheim et al, 2018).…”
Section: Perceptual Learning and The Recognition Of Degraded Speechmentioning
confidence: 99%
See 2 more Smart Citations
“…Although highly compressed speech is initially hard to recognize, recognition accuracy improves quite rapidly with exposure to as few as 10 to 20 time-compressed sentences (e.g., Dupoux & Green, 1997;Golomb et al, 2007). This rapid learning has been shown in young and in older adults as well as in older adults with hearing impairments (Golomb et al, 2007;Manheim et al, 2018;Peelle & Wingfield, 2005). Finally, across age and hearing levels, we previously reported that variance in rapid learning of TCS accounted for unique variance in the recognition of NFS, even after controlling for the known association between the recognition of NFS and TCS (Manheim et al, 2018).…”
Section: Perceptual Learning and The Recognition Of Degraded Speechmentioning
confidence: 99%
“…As for learning, perceptual learning for speech is certainly present in older adults with either normal or impaired hearing (Colby et al, 2018;Golomb et al, 2007;Karawani et al, 2016;Manheim et al, 2018;Neger et al, 2014;Peelle & Wingfield, 2005;Schlueter et al, 2016). However, whereas some reported little or no effects of age on learning (Golomb et al, 2007;Peelle & Wingfield, 2005), others found that learning might slow (Manheim et al, 2018) or diminish (Neger et al, 2014) with age. One possibility is that learning is maintained to a greater extent in situations in which lexical information can be used (Colby et al, 2018;Scharenborg & Janse, 2013).…”
Section: Age-related Hearing Loss Perceptual Learning and The Recogmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, we found that individual differences in rapid perceptual learning of one type of distorted speech (e.g., time-compressed speech) were consistently related to individual differences in speech perception under different adverse conditions (e.g., speech in noise) Karawani et al, 2017;Manheim et al, 2018;Rotman et al, 2020). Furthermore, these associations could not be explained by correlations in performance across adverse conditions.…”
Section: Rapid Learning Versus Perception Of Independent Adverse Speech Conditionsmentioning
confidence: 78%
“…are met (Manheim, Lavie, & Banai, 2018;Rotman, Lavie, & Banai, 2020). Consistent with this hypothesis, a recent study of visual tasks and auditory frequency discrimination suggests that a common perceptual learning factor accounts for approximately 30% of the variance across different learning conditions (Yang et al, 2020), but whether the same holds true for rapid learning of speech is at present unclear.…”
mentioning
confidence: 89%